The Effect of Reciting Holy Qur'an Toward Short-Term Memory - Indri Seta Septadina; Elpita Miftahul Jannah; Puji Rizky Suryani (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Working memory is a short-term memory that persists for seconds or minutes and can be stored in long-term memory. Murottal Qur'an is a recording of the recitation of the Qur'an, which is voiced by a Qori '(reader of the Qur'an) rhythmically. The recitation of the holy verses of the Qur'an by a Qori' is played through a zoom meeting by paying attention to recitation, which has a certain rhythm so it can stimulate activation in the brain area. This study aims to analyze the effect of the reciting Holy Qur'an on working memory in students of the Medical Education Study Program, Faculty of Medicine, Sriwijaya University. An experimental study with a cross-sectional approach with one group pretest-posttest design was carried out from July to December 2020 through the Zoom meeting application. The pretest and posttest examinations used in this study were digit span examinations, in the form of tasks containing digits forward and digits backwards before and after receiving the audio of Al-Qur'an intervention for seven days at 22.00. The data were tested for normality by Shapiro-Wilk, then analyzed using the Paired t-test or Wilcoxon using the Statistical Package for the Social Sciences (SPSS) program. Forty-five students are the research subjects. The results of the Wilcoxon test showed significant results of reciting the Holy Qur'an on working memory (p= 0.000) in students of the Medical Education Study Program, Faculty of Medicine, Sriwijaya University.Memori kerja adalah bentuk memori jangka pendek yang bertahan biasanya dalam hitungan detik atau menit atau dapat disimpan dalam memori jangka panjang. Murottal qur’an adalah rekaman bacaan al-qur’an yang disuarakan oleh seorang Qori’ (pembaca al-qur’an) dengan berirama. Lantunan ayat-ayat suci al-qur’an oleh seorang Qori’ yang diperdengarkan melalui zoom meeting dengan memperhatikan tajwid dan tartil yang mempunyai ritme tertentu sehingga dapat merangsang aktivasi pada area otak. Penelitian ini bertujuan untuk menganalisis pengaruh murottal qur’an terhadap memori kerja pada mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sriwijaya. Penelitian ini menggunakan jenis penelitian eksperimental dengan pendekatan cross-sectional with one group pretest-posttest design melalui aplikasi Zoom meeting. Pemeriksaan pretest dan posttest yang digunakan dalam penelitian ini adalah pemeriksaan digit span, berupa tugas yang berisi digits forward dan digits backward pada sebelum dan sesudah mendapatkan intervensi murottal Al-Qur’an selama 7 hari berturut-turut pada jam 22.00. Pada data dilakukan uji normalitas Shapiro-Wilk, selanjutnya dianalisis dengan menggunakan uji Paired t-test atau Wilcoxon menggunakan program Statistical Package for the Social Sciences (SPSS). Terdapat 45 mahasiswa yang menjadi subjek penelitian. Hasil dari uji Wilcoxon didapatkan hasil signifikan murottal al-Qur’an terhadap memori kerja (p=0,000) pada mahasiswa Program Studi Pendidikan Dokter Fakultas Kedokteran Universitas Sriwijaya.